Pharmaceutical sector of Bangladesh: prospects and challenges - Anesary, Md. Abdul Wadud; Hossain, Md. Jamil; Mamun, Md. Razib Al; Salam, MGA; Rahman, Khandaker Saifur; Morshed, Mohammad Monjur; Rahman, Md. Mahfuzur; Akter, Surya; Md. Waheduzzaman; Kabir, Zobayer Mohsin; Hassan, Sharif; Laboni, Sanjana; et al. (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.